Pengaruh Penerapan Peraturan Otoritas Jasa Keuangan Nomor 55 /Pojk.04/2015 Terhadap Tindakan Manajemen Laba - Krisna Irawan; Yulius Jogi Christiawan (Business Accounting Review, 2021)
This study aims to determine the relationship between the level of application of Financial Services Authority Regulations Number 55/POJK.04/2015, leverage, company size, and company growth on earnings management actions in all companies listed on the Indonesia Stock Exchange (IDX). The sample used in this study was 231 companies from 2013 to 2018. The amount data from this study was 1386 firm-years. The analytical echnique used in this study was panel data regression using Gretl application software (Gnu Regression, Econometrics, and Time-Series Library) with the selected estimation model is weighted least square model.The results of the study reveal that the higher the application of Financial Services Authority Regulations Number 55/POJK.04/2015, leverage, and company growth, the higher the earnings management actions, while the higher the firm size, the lower the earnings management actions.